(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This research examines the role of Communicative Language Teaching (CLT) in ESL classrooms and its influence on learners’ communicative development. The study aims to analyze how communicative tasks affect students’ motivation, participation, and language performance. A qualitative approach was used, involving classroom observations, questionnaires, and informal interviews. The results demonstrate that CLT significantly improves students’ speaking confidence, interaction skills, and overall engagement in the learning process. The findings also suggest that CLT creates a supportive learning environment that encourages learners to use English more actively.